A secure cryptosystem using DNA cryptography and DNA steganography for the cloud-based IoT infrastructure. (December 2022) - Namasudra, Suyel
Highlights: A novel cryptosystem is proposed by using DNA computing in the cloud-based IoT infrastructure. The proposed cryptosystem embeds the encrypted data in a cover image in the form of a long DNA sequence prior to storing it on the cloud server. This novel cryptosystem is secure against many security attacks. Experimental results prove the efficiency of the proposed cryptosystem over the existing cryptosystems. Abstract: In this digital era, most of the data of an Internet of Things (IoT) infrastructure are communicated over the internet and they are stored in a cloud environment. As there are numerous users and attackers over the internet, IoT data face many security issues. Currently, Deoxyribonucleic Acid (DNA) cryptography is a cutting-edge area, which is used to enhance data security. In this paper, a novel cryptosystem is proposed using DNA cryptography and DNA steganography for the cloud-based IoT infrastructure. Here, the confidential data is encrypted by using a long secret key. Then, it is hidden in an image. Thus, the proposed cryptosystem not only hides the data, but also encrypts the confidential data prior to storing it on the cloud server, and it resists many security attacks in the cloud-based IoT infrastructure. To evaluate the performance of the proposed scheme, many experiments are performed. The results show the effectiveness of the proposed scheme. Graphical abstract: Image, graphical abstract